2021
DOI: 10.3389/fpsyg.2021.706149
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Attitudes Toward Casual Sex: Using STI Contraction Likelihoods to Assess Evolved Mating Strategies

Abstract: Previous work shows that males are more likely to pursue casual sex if given the opportunity, compared to females, on average. One component of this strategy is risk-taking, and males have been shown to take more risks than females in a variety of contexts. Here, we investigate the extent to which sex differences exist considering casual sexual encounters involving sexually transmitted infections (STIs) using a hypothetical sexual scenario which attempts to circumvent several factors that may contribute to a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Men were significantly more unrestricted than women in all three facets of sociosexuality: in behavior, attitude, and desire. In fact, consistent data suggest that males are more willing to incur risks associated with sexually transmitted infection contraction when considering short-term sexual encounters (Pipitone et al, 2021). However, some studies (Penke & Asendorpf, 2008;Price et al, 2013;Timmers & Chivers, 2012) revealed that sex differences were most pronounced in sociosexual desire, smaller for attitude, and not traceable for the behavior facet.…”
Section: Discussionmentioning
confidence: 99%
“…Men were significantly more unrestricted than women in all three facets of sociosexuality: in behavior, attitude, and desire. In fact, consistent data suggest that males are more willing to incur risks associated with sexually transmitted infection contraction when considering short-term sexual encounters (Pipitone et al, 2021). However, some studies (Penke & Asendorpf, 2008;Price et al, 2013;Timmers & Chivers, 2012) revealed that sex differences were most pronounced in sociosexual desire, smaller for attitude, and not traceable for the behavior facet.…”
Section: Discussionmentioning
confidence: 99%
“…Men might behave in ways which favor STRR over LTRR. Relative to women, men exhibit stronger sex drives (Frankenbach et al, 2022), embrace casual sex (Archer, 2019;Buss & Schmitt, 2019), and take higher risks for it (Pipitone et al, 2021). They show curiosity in diverse sexual experiences (Gray et al, 2019;Thompson et al, 2020), including threesomes and one-night stands.…”
Section: The Concept Of Short-term and Long-term Romantic Relationshipsmentioning
confidence: 99%